SPIRITUAL AND CULTURAL REFORMS IN HIGHER EDUCATION IN NEW UZBEKISTAN (Spectrum Journal of Innovation, Reforms and Development, 2025)
The article analyzes the spiritual and cultural reforms being implemented in higher education institutions during the "New Uzbekistan" period. The need to strengthen spirituality and national values in the education system, the impact of globalization, and shortcomings in the spiritual formation of young people are considered. New programs introduced in higher education institutions, the role of disciplines such as "Spirituality and Enlightenment", measures to improve the moral education of students, as well as measures to preserve and develop cultural heritage are highlighted. The importance of spiritual and educational exchange through international cooperation is emphasized, and the role of reforms in the development of society is assessed.